Pengaruh Kualitas Layanan Farmasi Terhadap Kepuasan Pasien Pada Pasien di Rumah Sakit Tipe D Yogyakarta - Winanti Winanti (Jurnal Admmirasi, 2021)
Hospital pharmaceutical installation services play an important role in efforts to improve the quality of hospital services. The quality of hospital services affects patient satisfaction. This study aims to determine the effect of pharmaceutical service quality on outpatient satisfaction at D type Hospital in Yogyakarta. This type of research is quantitative. The population is all outpatients in D type Hospital. Retrieval of data using a questionnaire. Multivariate data analysis using multiple regression analysis. The results showed that the dimensions of pharmaceutical service quality that influence patient satisfaction are tangible. Dimensions of pharmaceutical service quality that do not affect patient satisfaction are reliability, responsiveness, assurance and empathy. In conclusion, pharmaceutical service quality (reliability, responsiveness, certainty, empathy and tangible manifestations) affect patient satisfaction with pharmaceutical services at D type Hospital Yogyakarta (t 7,239; p 0,000).